2023
DOI: 10.3389/fimmu.2023.1185618
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 downregulation improves sensitivity and endurance of CAR T cell functional capacities

Abstract: Chimeric antigen receptor (CAR) modified T cells can induce complete remissions in patients with advanced hematological malignancies. Nevertheless, the efficacy is mostly transient and remains so far poor in the treatment of solid tumors. Crucial barriers to long-term CAR T cell success encompass loss of functional capacities known as “exhaustion”, among others. To extend CAR T cell functionality, we reduced interferon regulatory factor 4 (IRF4) levels in CAR T cells using a one-vector system encoding a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The hypoxic and acidic conditions within solid tumors also negatively impact the functionality of CAR-T cells, contributing to their rapid exhaustion [ 12 ]. Numerous studies have also highlighted the role of multiple transcription factors as contributors to CAR-T cell exhaustion within solid tumors; these factors include Thymocyte selection-associated high mobility group box protein (TOX), interferon regulatory factor (IRF4), Nuclear factor of activated T cells (NFATs), and Myeloblastosis transcription factors (MYBs) [ 13 , 14 , 15 , 16 ]. In addition, not only long-term resistance but also short-term tumor adaptation to CAR is a problem.…”
Section: Challenges Of Using Car-t Therapy For Solid Tumorsmentioning
confidence: 99%
“…The hypoxic and acidic conditions within solid tumors also negatively impact the functionality of CAR-T cells, contributing to their rapid exhaustion [ 12 ]. Numerous studies have also highlighted the role of multiple transcription factors as contributors to CAR-T cell exhaustion within solid tumors; these factors include Thymocyte selection-associated high mobility group box protein (TOX), interferon regulatory factor (IRF4), Nuclear factor of activated T cells (NFATs), and Myeloblastosis transcription factors (MYBs) [ 13 , 14 , 15 , 16 ]. In addition, not only long-term resistance but also short-term tumor adaptation to CAR is a problem.…”
Section: Challenges Of Using Car-t Therapy For Solid Tumorsmentioning
confidence: 99%
“…Recently, we reported that downregulation of the transcription factor interferon regulatory factor-4 (IRF4) improved antigen sensitivity which enabled CAR T cells to target antigen low pancreatic cancer cells that are not recognized by CAR T cells with physiological IRF4 levels ( 48 ). IRF4 downregulation provoked an overall increase in T cell activation in response to antigen low pancreatic cancer cells reflected by the upregulation of members of the IL-2 signaling pathway, such as CD25 and phospho-STAT5 ( 48 ).…”
Section: Engineering Signaling Checkpointsmentioning
confidence: 99%
“…Recently, we reported that downregulation of the transcription factor interferon regulatory factor-4 (IRF4) improved antigen sensitivity which enabled CAR T cells to target antigen low pancreatic cancer cells that are not recognized by CAR T cells with physiological IRF4 levels ( 48 ). IRF4 downregulation provoked an overall increase in T cell activation in response to antigen low pancreatic cancer cells reflected by the upregulation of members of the IL-2 signaling pathway, such as CD25 and phospho-STAT5 ( 48 ). We hypothesized that a direct increase in c-Jun-mediated transcriptional activation of target genes, such as IL-2, through displacing AP1-IRF4 complexes from chromatin is likely the driving factor, similar to the effects obtained by c-Jun overexpression.…”
Section: Engineering Signaling Checkpointsmentioning
confidence: 99%